Dental anxiety – causes, characteristics and occurrence in the Polish population - Rosiak, Joanna; Szymańska, Jolanta (Current Problems of Psychiatry, 2017)
The present paper discusses the problem of dental anxiety. Based on the scientific review of Polish literature of the past 10 years, there are discussed causes of dental anxiety in different age groups and the methods of assessing the level of anxiety – physiological, behavioral, projection and psychological. Dental anxiety affects the patients’ attitude towards their own health, confidence in dentist, the frequency of reporting to the dental prophylaxis and treatment, which translates into oral health. It is also a major impediment to everyday clinical practice of a dentist.